Bibliokonseling Sebagai Teknik dalam Pencegahan Pelecehan Seksual di Sekolah Menengah Pertama - Bakhrudin All Habsy; Mochamad Nursalim; Budi Purwoko; Miftahul Amanah (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
This research begins with the phenomenon of teenagers who do not understand enough about preventing sexual harassment, so many become victims. Victims of sexual harassment experience negative impacts physically, psychologically, and even affect their social life. Physical impacts can include injuries to parts of the body, tears to the hymen for female victims, and much more. Then on the psychological impact, the victim can feel anger, stress, have the desire to commit suicide, and even be afraid when they meet other people with the same physical characteristics as the perpetrator. For this reason, counselors certainly need appropriate techniques and methods to help students prevent sexual harassment with knowledge through bibliocounseling techniques. Based on the results of the ideas/study of the discussion above relating to the use of biblio-counseling as an effort to prevent sexual harassment in the school environment, the use is able to educate individuals to develop a deeper understanding of themselves, gain new insights, and find solutions to life's challenges through literature. and guidance. Analysis of this research data is presented in groups and individuals in discussion. The research subjects were junior high school students, who needed education about how to prevent sexual harassment.The results of the analysis of this research regarding the prevention of sexual harassment using biblio-counseling techniques show that there is a difference between before and after being given biblio-counseling regarding the prevention of sexual harassment in the school environment. This means that the treatment of biblio-counseling techniques has a positive effect on students who experience a lack of knowledge about sexual harassment. So it can be concluded that providing bibliocounseling technique treatment can increase the prevention of sexual harassment in junior high schools.